Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 2 - Section 2.3 - Calculating Limits Using the Limit Laws - 2.3 Exercises: 17


$\lim\limits_{h\to 0}\frac{(-5+h)^2-25}{h}=-10$

Work Step by Step

$\lim\limits_{h\to 0}\frac{(-5+h)^2-25}{h}$ $=\lim\limits_{h\to 0}\frac{(25+h^2-10h)-25}{h}$ (we use $(a-b)^2=a^2-2ab+b^2$) $=\lim\limits_{h\to 0}\frac{h^2-10h}{h}$ $=\lim\limits_{h\to 0}\frac{h(h-10)}{h}$ (factorize the numerator) $=\lim\limits_{h\to 0}(h-10)$ (divide both the numerator and denominator by $h$) $=0-10$ $=-10$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.